Stalinism : Russian and Western views at the turn of the millennium - Litvin, Alter L. (Routledge, 2005)
Stalinism surveys the efforts made in recent years by professional historians, in Russia and the West, to better understand what really went on in the USSR between 1929 and 1953.
Keywords: Stalin, Joseph, -- 1878-1953.; Stalin, Joseph, -- 1879-1953.; Stalin, Joseph, -- 1878-1953; Soviet Union -- History -- 1925-1953.; URSS -- Histoire -- 1925-1953.; HISTORY.; Soviet Union; Russia & Former Soviet Republics.; Regions & Countries - Europe.; History & Archaeology.; 1925-1953; History